Perlindungan Hukum Pemisahan Harta Pasca Perkawinan jika Terjadi Kepailitan pada Suami Istri - Christian Simarmata, Thesalonica; Subekti, Sri (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This research was made because there are still many people who do not understand the marriage agreement for separation of assets. Especially for people who enter into reciprocal agreements between creditors and debtors, where there are still people who are married debtors who do not have marriage agreements to separate assets. Bankruptcy occurs due to several factors, both individual and individual. A person is declared bankrupt if it is based on a commercial court decision which has direct legal consequences. One of them is the legal impact of a bankruptcy decision on the assets of a husband and wife, whether the husband is a bankrupt debtor or a wife who is a bankrupt debtor. Problems will arise because basically the concept of marriage or matrimony in Indonesia applies the concept of joint property, unless it is agreed separately before the marriage through a prenuptial agreement or prenuptial agreement regarding the separation of assets. Moreover, there are provisions in Marriage Law Number 16 of 2019 regarding amendments to Marriage Law Number 1 of 1974 concerning Marriage, provisions in Article 29 which state that an agreement for separation of assets can only be made before difficulties arise for married couples who are not yet familiar with an agreement for separation of assets. In connection with this, the Constitutional Court issued MK Decision No.69/PU-XIII/2015 which amended the provisions of Article 29 of the Marriage Law